Nilai-Nilai Islam Dan Estetika Yang Terdapat Pada Lampu Colok Pada Malam 27 Ramadhan Di Desa Pedekik Kecamatan Bengkalis - Setiawan, Agus; Kurniati, Wilda; Zamrizal, Zamrizal (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
Indonesia has cultural diversity that is recognized by UNESCO, one of which is the cultural heritage from Pedekik Village, Bengkalis District, namely the plug lamp. Pedekik Village was formed in 1980 with an area of ​​20 km2 with a population of 2556 people, 1316 men and 1240 women with a population density of 124 people. At first, the community only used plug-in lamps as street lighting and home decoration. Along with the development of the times, plug-in lights have changed in the form of miniature images such as Allah's names, prayer rooms, mosques, and the Kaaba which are lit on the night of 27 Ramadan. The purpose of the research conducted was to find out the values ​​contained in the plug-in lamps in Pedekik Village. So the use of qualitative methods and the data used are primary and secondary data. From the research results, there are two values: Islamic and aesthetic. Islamic values ​​are in the form of divine values, worship values, Aqidah values ​​and moral values. While the subjective aesthetic value is in the form of an idea that is poured into the design and the objective aesthetic value is in the form of a miniature plug-in lamp.